Coracini, M. J. (org). Identidade & discurso. Campinas: Editora da Unicamp: Argos Editora Universitária, 2003, 385 págs. - Costa, Francisco Vanderlei (Cadernos de Linguagem e Sociedade, 2010)
Coracini, M. J. (org). Identidade & discurso. Campinas: Editora da Unicamp: Argos Editora Universitária, 2003, 385 págs.